Reformulation of Da’wah Communication Paradigm in the Post-Pandemic Era - Ries Dyah Fitriyah; Sokhi Huda; Abd. Mujib Adnan; Tantan Hermansah; Athik Hidayatul Ummah (Jurnal Komunikasi Islam, 2022)
This study focuses on examining the challenges and needs for the reformulation of the da'wah and communication paradigm in the post-pandemic era. Through a qualitative approach, the results of this study show that in the post-pandemic era, da'wah requires a redefinition and reformulation of paradigms, known as the happy da'wah paradigm, namely placing happiness in the experience of the da'wah process and the practice of religious teachings, not on the purpose of da'wah. The performance of the activity system is directed to "offer" the da'wah message, not to "impose" the message. The appearance and performance of this system is packaged in an attractive, creative, innovative, supportive and affirmative communication pattern by utilizing information technology as an efficient communication medium.